Only the dead : a thriller [large type] - Carr, Jack (Joint pseudonym) (Carr, Jack (Joint pseudonym). Terminal list (Series), 2023)
"In 1980, a freshman congressman was gunned down in Rhode Island, sending shockwaves through Washington that are still reverberating over four decades later. Now, with the world on the brink of war and a weakened United States facing rampant inflation, political division, and shocking assassinations, a secret cabal of global elites is ready to assume control. And with the world's most dangerous man locked in solitary confinement, the conspirators believe the final obstacle to complete domination has been eliminated. They're wrong. From the firms of Wall Street to the corridors of power in Washington, DC, and Moscow, secrets from the past have the uncanny ability to rise to the surface in the present. With the odds stacked against him, James Reece is on a mission generations in the making. Unfortunately for his enemies, the former SEAL is not concerned with odds. He is on the warpath. And when James Reece picks up his tomahawk and sniper rifle, no one is out of range."--